KETERAMPILAN METAKOGNISI DIKAJI DARI HASIL BELAJAR DALAM MATERI PERSAMAAN KUADRAT DI SEKOLAH MENENGAH ATAS - Yanto, Fransiskus; Suratman, Dede; Yani, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to describe how metacognition skills are assessed from student learning outcomes in class XII quadratic equation material at SMA St. Fransiskus Asisi Pontianak. The research method is descriptive with the survey. The subjects of this study were six students of class XII Natural Sciences which consisted of two students with high learning outcomes, two students with moderate learning outcomes, and two students with low learning outcomes. The results of this study indicate that metacognition skills for learning outcomes are high, almost all indicators are fulfilled in every planning, monitoring, and evaluation. While metacognition skills for learning outcomes are moderate, only planning and monitoring indicators are met, evaluation is still lacking. There for metacognition skills for learning outcomes are low, only planning indicators are met, monitoring and evaluating is still lacking.Keyword : Metacognition Skill, Learning outcomes, Quadratic Equation